Mono- and Biallelic Protein-Truncating Variants in Alpha-Actinin 2 Cause Cardiomyopathy Through Distinct Mechanisms. (22nd November 2021) - Lindholm, Malene E.; Jimenez-Morales, David; Zhu, Han; Seo, Kinya; Amar, David; Zhao, Chunli; Raja, Archana; Madhvani, Roshni; Abramowitz, Sarah; Espenel, Cedric; Sutton, Shirley; Caleshu, Colleen; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: ACTN2 (alpha-actinin 2) anchors actin within cardiac sarcomeres. The mechanisms linking ACTN2 mutations to myocardial disease phenotypes are unknown. Here, we characterize patients with novel ACTN2 mutations to reveal insights into the physiological function of ACTN2. Methods: Patients harboring ACTN2 protein-truncating variants were identified using a custom mutation pipeline. In patient-derived iPSC-cardiomyocytes, we investigated transcriptional profiles using RNA sequencing, contractile properties using video-based edge detection, and cellular hypertrophy using immunohistochemistry. Structural changes were analyzed through electron microscopy. For mechanistic studies, we used co-immunoprecipitation for ACTN2, followed by mass-spectrometry to investigate protein-protein interaction, and protein tagging followed by confocal microscopy to investigate introduction of truncated ACTN2 into the sarcomeres. Results: Patient-derived iPSC-cardiomyocytes were hypertrophic, displayed sarcomeric structural disarray, impaired contractility, and aberrant Ca 2+ -signaling. In heterozygous indel cells, the truncated protein incorporates into cardiac sarcomeres, leading to aberrant Z-disc ultrastructure. In homozygous stop-gain cells, affinity-purification mass-spectrometry reveals an intricate ACTN2 interactome with sarcomere and sarcolemma-associated proteins. Loss of the C-terminus of ACTN2 disrupts interaction with ACTN1 (alpha-actinin 1) and GJA1 (gap junction protein alpha 1), 2 sarcolemma-associated proteins, which may contribute to the clinical arrhythmic and relaxation defects. The causality of the stop-gain mutation was verified using CRISPR-Cas9 gene editing. Conclusions: Together, these data advance our understanding of the role of ACTN2 in the human heart and establish recessive inheritance of ACTN2 truncation as causative of disease.